Multiple Sclerosis : Diagnosis and Therapy - Weiner, Howard L.; Stankiewicz, James M. (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2012)
Designed for both neurologists and non-neurologists, Multiple Sclerosis: Diagnosis and Therapy takes a practical approach to the most current principles of diagnosis and management of this complex disease. Editors and authors from Harvard Medical School have contributed up-to-date therapeutic information for the various stages and types of MS and also provide the necessary background regarding the pathogenesis of the disease.
Disease pathogenesis / Roopali Gandhi and Howard L. Weiner -- Biomarkers / Manuel Comabella and Samia J. Khoury -- Epidemiology and genetics / Philip L. De Jager -- Diagnosis / James M. Stankiewicz, Varun Chaubal, and Guy J. Buckle -- Pediatric multiple sclerosis, and acute disseminated encephalomyelitis / Tanuja Chitnis -- Magnetic resonance imaging in multiple sclerosis / Mohit Neema [and others] -- Predicting clinical course / Brian Healy and Maria Liguori -- Medication treatment in multiple sclerosis / James M. Stankiewicz and Samia J. Khoury -- Symptom management / Lynn Stazzone and Brandon Brown -- Cognitive dysfunction in multiple sclerosis / Bonnie I. Glanz and Maria K. Houtchens -- Depression and other psychosocial issues in multiple sclerosis / David J. Rintell -- Future therapeutic approaches / Howard L. Weiner and Laura Edwards.
Includes bibliographical references and index.
Print version record.
Keywords: Multiple sclerosis -- Diagnosis; Multiple sclerosis -- Treatment; Multiple sclerosis; Multiple Sclerosis -- nursing; Multiple Sclerosis -- psychology; Medicine; HEALTH & FITNESS -- Diseases -- Alzheimer's & Dementia; MEDICAL -- Neurology; Multiple sclerosis; Multiple sclerosis -- Diagnosis; Multiple sclerosis -- Treatment; Electronic books